Digital Transformation Readiness in Higher Education Institutions (HEI): The Case of Kosovo. Issue 25 (2019) - Limani, Ylber; Hajrizi, Edmond; Stapleton, Larry; Retkoceri, Murat
Abstract: This research investigates the current readiness of Higher Education Institutions for the digital transformation of their processes. The purpose of the study is to investigate the implemented comparative measures and the challenges faced by higher education institutions dealing with the digital transformation of their processes. The specific importance of this study relates to the level of use of digital technologies during the teaching process as well as administrative activities that enable advanced communication between institutions, students, academic and administrative staff, as well as other internal and external networking processes. The research results show a significant change in the particular interest in the use of digital technologies at HEIs. The major digital transformation technologies such as Artificial Intelligence, Cloud Technologies, Internet of Things, undergone comparison and ranking based on the findings from the best practices derived from literature. The same ranking has been conducted at the HEI of Kosovo. The synthesis of two evaluations delivers the final results of this research.